Studies on the susceptibility of pear trees to pear psylla, Psylla pyricola Foerster (Homoptera: Psyllidae). - Chang, Juan F. F. (University of Ottawa (Canada), 1977)
Development and behaviour of the pear psylla, Psylla pyricola Foerster, were observed under field and laboratory conditions. Bioassay chambers were used in the laboratory to determine the susceptibility of different taxa of pear to pear psylla attack. The selected plant material and the insects were collected from the field, at the Jordan Experimental Farm, Jordan Station, Ontario. Psylla behaviour in the chambers was compared to field observations and in both cases most adult pear psylla migrated to the leaves of pear by early evening. Pear psylla tested on different plant species and different cultivars of pear did not show significant differences in the relative number of insects per plant species or cultivar. Psylla produced frass in a consistent and reproducible manner on the different taxa tested. Frass deposition was also accompanied by egg laying in the majority of cases. Results indicate that pear psylla fed differentially on the different plants tested. Pear psylla development in the field after 21 days was also observed and the data recorded from it paralleled the data obtained for the same plants tested under bioassay conditions in the laboratory. A cursory analysis of lipid and polar soluble phenolic compounds was performed. The ratio of the common number over the total number of different polar phenolics between the two taxa compared shows a grouping trend among the taxa tested, which is similar to the results from the bioassays and the field study. According to the results obtained in the field, in bioassays, and two-dimensional chromatography of phenolic compounds in the plants tested, these plants can be arranged in three categories: (1) most preferred hosts for Psylla pyricola (Bosc and Old Home), (2) intermediate hosts (Bartlett, Kieffer, and d'Anjou), and (3) least preferred hosts (Clapp, P. ussuriensis, and quince). The present work indicates that pear psylla, tested on the Niagara Peninsula, is a specific pest of the pear crop, but it could feed on quince under unfavorable conditions. The analysis of phenolic compounds indicates that there is definite number of phenolic compounds associated with the susceptibility of the plant successfully attacked by Psylla pyricola .
Keywords: Agriculture, Plant Pathology.